School‐age children enjoyed good respiratory health and fewer allergies despite having lung disease after preterm birth. (12th August 2016) - Ronkainen, Eveliina; Kaukola, Tuula; Marttila, Riitta; Hallman, Mikko; Dunder, Teija
Abstract: Aim: This study explored the under‐researched area of whether preterm birth or bronchopulmonary dysplasia (BPD) affected hospitalisation rates, allergies or health‐related quality of life (HRQoL). Methods: We studied 88 schoolchildren born preterm at a mean gestational age of 28.8 weeks (range 24.1–31.9) and matched term‐born controls at the mean age of 11 years (range 8–14). Hospitalisations after the first discharge were recorded, skin prick allergy tests were performed and HRQoL was assessed with a parental questionnaire. Results: Preterm children were hospitalised more than controls (64% versus 39%, p = 0.001), mostly before two years of age. The adjusted odds ratios (OR) for two‐year‐old preterm‐born children being hospitalised for wheezing was 8.2 (95% CI 2.0–34.1). BPD affected 56% of the preterm children, but did not influence hospitalisations, and the positive skin prick rate was similar between the preterm and term‐born children (35% versus 48%, p = 0.126). Preterm BPD children had fewer positive skin prick tests than those without BPD. HRQoL was lower in preterm than term children (81.25 ± 10.84 versus 86.80 ± 9.60, p = 0.001). Conclusion: Most health problems experienced by preterm‐born schoolchildren occurred before two years of age and were mainly wheezing disorders. BPD decreased atopy but had no influence on hospitalisation rates.